Determining the depth and upwelling speed of the equatorial Ekman layer from surface drifter trajectories - Paldor, Nathan; De-Leon, Yair (Ocean science, 2025)
In this work, trajectories of more than 500 drogued surface drifters launched in the equatorial ocean since 1979 are analyzed by employing the results of a new Lagrangian theory of poleward transport from the Equator forced by the prevailing trade winds. The Lagrangian theory provides an explicit expression for the depth of the Ekman layer that circumvents the application of the 3D continuity equation that requires calculation of the divergence of horizontal transport, which has been the basis of all previous studies on the subject. The analysis is carried out for drifters launched within 1° of the Equator that reached a final latitude of 3, 4, or 5° north or south of the Equator while also remaining in one hemisphere throughout their entire travel time. The analysis yields robust estimates of 45 m for the Ekman layer's depth and 1.0 m d−1 for the upwelling speed of thermocline water into the layer.